Time-frequency analysis on seismic response and pre-toppling damage evolution of anti-dip rock slope under earthquake sequences by shaking table tests - Yan, Kongming; Wang, Gonghui; Nikitas, Nikolaos; Bao, Ning; Doi, Issei; Tao, Zhigang (Engineering geology, 2025)
Anti-dip rock slopes in tectonically active regions are highly susceptible to seismic loading. While their response to individual mainshocks has been widely studied, the cumulative effect of sequential earthquakes, particularly in relation to gradual, subvisible damage preceding visible toppling, remains underexplored. This study employs a large-scale shaking table test to investigate both internal and external seismic responses and the damage progression of a generalized anti-dip slope model in the time and frequency domains. Results indicate that slope acceleration initially exhibits a linear amplification pattern but transitions to nonlinear behaviour as seismic intensity increases, with the free-face effect diminishing at higher intensities. Dominant frequency nonlinearly shifts and seismic energy variations correlate with both slope height and increasing seismic loads, while a decrease in natural frequency and an increase in damping ratio revealed by transfer function analysis, typically representative of internal damage accumulation. Notably, the major damage of the rock slope model occurs during the mainshock sequence, with subsequent aftershocks exerting limited further impact. Under sequentially increasing seismic loading, slope surface deformation initiates with bulging at the toe, intensifies toward the crest, and is accompanied by uneven settlement at the top. Internal strain readings further reveal progressive bending of rock strata in response to increasing seismic input, characteristic of pre-toppling deformation. These findings provide critical insights for early warning and risk evaluation of anti-dip rock slope stability, by offering a basis for identifying pre-toppling characteristics prior to a complex and visible toppling failure. •Dynamic amplification transitions from linear to nonlinear with excitation increase.•Pre-toppling under earthquake sequences involves a progressive damage process.•Time-frequency variations enhance early warning for slope instability assessment.